Acute myocardial infarction in cocaine induced chest pain presenting as an emergency. Issue 2 (1st March 2003) - Carley, Simon; Ali, Baha; Mackway-Jones, K
Abstract : A short cut review was carried out to establish the incidence of acute myocardial infarction in patients presenting as emergencies with post-cocaine chest pain. Altogether 198 papers were found using the reported search, of which eight presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results, and study weaknesses of these best papers are tabulated. A clinical bottom line is stated.